MENINGKATKAN HASIL BELAJAR SOAL CERITA MELALUI PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA SISWA KELAS 5 SEKOLAH DASAR NEGERI 018 GERBANG SARI - Ahmad Karim (Journal of Education and Teaching, 2020)
This study aims to improve the learning outcomes of storytelling through a contextual teaching and learning (CTL) approach in grade 5 students of state elementary schools 018 gateway sari kecaptung hilir district. Kampar. The concept of learning that emphasizes the relationship between learning material with the real world of student life. So students are able to connect and apply learning outcomes competencies in everyday life. This research is a classroom action research using observation, library study and cycle performance assessment. The results showed the Contextual Teaching and Learning (CTL) approach can improve student learning outcomes in Mathematics subjects. This can be seen in the results of the study which showed that in cycle I students completed 16 people 80% while students who did not complete 4 people 18%. Likewise, this approach can increase students' enthusiasm in learning so that the classroom atmosphere when the teaching and learning process becomes more lively and the implementation of learning story questions through the CTL approach consists of 7 steps of the CTL approach and combined with the steps to solve the story problems. Learning using the CTL approach can be divided into three stages: the initial stage, the core stage, and the final stage. In the initial stage the activities of activating students' initial knowledge are carried out, conveying learning objectives, and apperception. At the core stage CTL steps are carried out namely constructivism, inquiry, asking questions, learning communities, modeling, reflection, and actual assessment. In the final stages of activity students are directed to conclude learning and provide a final test. In conclusion students are motivated to learn, because students will be active in learning, foster a sense of cooperation in groups, learning outcomes can be measured in various ways, and make learning more fun and meaningful for students